Investigating differentiated learning of mathematics lessons in islamic schools: A systematic literature review - Yuni Dewi Purnamasari (12 Waiheru, 2025)
This study aims to systematically examine the implementation of differentiated instruction in Islamic schools, particularly in mathematics education. The research method employed is a Systematic Literature Review (SLR) consisting of the following stages: identification, screening, eligibility assessment, and inclusion. Using the Publish or Perish application, 318 articles were retrieved with the keywords “differentiated instruction,” “instructional differentiation,” and “differentiated mathematics instruction” from Google Scholar, covering publications between 2019 and 2024. Seventeen articles were selected for further analysis and data extraction. The findings of the systematic literature review on differentiated instruction in mathematics education reveal several key points: (1) Research on differentiated instruction is predominantly conducted in East Java Province; (2) Differentiated instruction has been implemented, developed, and proven effective in mathematics education at Islamic schools; (3) The benefits of differentiated instruction include improved learning outcomes, increased student motivation, and enhanced student engagement during the learning process; (4) Research approaches include quantitative, qualitative, and research and development (R&D) methods; (5) Effectiveness assessments of differentiated instruction are conducted using questionnaires, tests, observations, and interviews; (6) Mathematical content explored in the context of differentiated instruction at Islamic schools includes Numbers and Geometry. This study contributes to the field of education by providing insights into the development of differentiated instruction, particularly in mathematics education at Islamic schools, within the context of Indonesia’s education system.